Breast milk oligosaccharides: effects of 2′-fucosyllactose and 6′-sialyllactose on the adhesion of Escherichia coli and Salmonella fyris to Caco-2 cells. (2nd September 2019) - Facinelli, Bruna; Marini, Emanuela; Magi, Gloria; Zampini, Lucia; Santoro, Lucia; Catassi, Carlo; Monachesi, Chiara; Gabrielli, Orazio; Coppa, Giovanni V.
Abstract: Background: It is well known that human milk oligosaccharides play an important role as prebiotics, anti-inflammatory, and anti-infective agents. In the last few years, several studies have been performed using specific oligosaccharides, such as 2′-fucosyllactose and 6′-sialylactose, to evaluate their biological functions. Objectives: The aim of the present study is to evaluate the anti-adhesive effect of the above oligosaccharides on Escherichia coli and Salmonella fyris . Methods: Adhesion experiments were performed in the presence of 2′-fucosyllactose and 6′-sialyllactose as potential inhibitors of Escherichia coli and Salmonella fyris adhesion to Caco-2 cells. The oligosaccharides were used at different concentrations and the adhesion experiments were performed in triplicate and repeated at least three times. Results: A significant reduction of Escherichia coli adhesion was observed in the presence of 2′-fucosyllactose and 6′-sialyllactose at the human milk concentration. On the contrary, no positive effects were observed in both oligosaccharides on Salmonella firis . Conclusions: Our results suggest that the supplementation in infant formulas of 2′-fucosyllactose and 6′-sialyllactose, actually commercially available and absent in cow milk, could play positive effects in artificially fed infants.